Absorption of macronutrients by cassava in different harvest dates and dosages of nitrogen - Santos, Nádia; Alves, José Maria; Uchôa, Sandra Catia; Oliveira, Natália; Albuquerque, José de Anchieta (Revista Ciência Agronômica, 2014)
A field experiment was carried out in 2010-2011 crop years in the experimental area of the Centro de Ciências Agrárias of the Universidade Federal de Roraima, in Boa Vista, Roraima, Brazil. This study aimed to evaluate the effect of nitrogen availability on the concentrations of N, P, K, Ca, Mg and S in cassava, cultivar Aciolina, in different harvest times. A randomized block design was used in split-plot, with four replications. Dosages of N in cover were applied randomly on the plots (0, 30, 60, 150 and 330 kg ha-1), and in the subplot the harvest dates 120, 150, 180, 210, 240, 270 and 300 days after emergence (DAE). The vegetal material was collected, ground and then underwent an analysis for determination of nutrients concentrations in the leaves (N, P, K, Ca Mg and S). The harvest dates and dosages of N affect the nutrient concentrations in the cassava leaves, cv. Aciolina. The macronutrients dosage in the leaves, 120 DAE, is a good indicator of the nutritional status of the cassava plant. The dosage of 150 kg ha-1 of N raises the tubers roots per plant. The sequence of the macronutrients concentration in the leaves of the cassava, cv. Aciolina is N>Ca>K>Mg>P>S.